The influence of affective touch on interoceptive and exteroceptive sensory integration in infants: evidence from heartbeat-evoked and event-related potentials - Tanaka, Yukari; Myowa, Masako (Frontiers in Psychology, 2025)
IntroductionThe daily accumulation of multimodal interactions with a primary caregiver is thought to integrate interoceptive and exteroceptive information in the infant brain, which may contribute to the development of social cognition. However, the neural mechanisms underlying this integration in infancy remain largely unexplored. Focusing on affective touch as a sensory stimulus affecting infants' interoception during caregiver-infant interactions, this study examined how the perception of affective touch (i.e., stroking) affects the neural processing of interoceptive-exteroceptive integration in infants' brains.MethodsDuring the exposure phase, infants' legs were stroked while viewing a stranger's face (Affective Touch, AT), while another face was presented without touch as a control (No-Affective Touch, No-AT). In the test phase, infants viewed the same faces in isolation. Electroencephalography (EEG) and electrocardiogram (ECG) were simultaneously measured to compare two neural indices between conditions in the test phase: heartbeat-evoked potentials (HEPs), reflecting interoceptive-exteroceptive integration, and event-related potentials (ERPs) to faces, indicating exteroceptive processing.ResultsResults showed that affective touch enhanced HEPs in frontal-central regions and modulated ERPs to faces, with stronger P400 amplitudes in parietal regions. In addition, a positive correlation between HEP responses and ERPs to faces emerged, with individual differences in resting HEP, reflecting baseline interoceptive-exteroceptive sensitivity, being associated with HEP modulation during the test phase.DiscussionThese findings suggest the role of multisensory experiences, particularly those involving touch, in enhancing interoceptive-exteroceptive integration, with individual variations. Our findings support the hypothesis that affective caregiver-infant interactions facilitate interoceptive-exteroceptive integration, a fundamental process underlying the development of social cognition, and emotional regulation.